Characterization of the key aroma compounds in pork soup stock by using an aroma extract dilution analysis. Issue 1 (2nd January 2014) - Takakura, Yukiko; Osanai, Hiroki; Masuzawa, Takuya; Wakabayashi, Hidehiko; Nishimura, Toshihide
Abstract: The aroma extract dilution analysis of an extract prepared from pork stock and subsequent experiments led to the identification of 15 aroma-active compounds in the flavor dilution factor range of 64–2048. Omission experiments to select the most aroma-active compounds from the 15 odor compounds suggested acetol, octanoic acid, δ-decalactone, and decanoic acid as the main active compounds contributing to the aroma of pork stock. Aroma recombination, addition, and omission experiments of these four aroma compounds in taste-reconstituted pork stock showed that each compound had an individual aroma profile. A comparison of the overall aroma between this recombined mixture and pork stock showed strong similarity, suggesting that the key aroma compounds had been successfully identified. Graphical abstract: : Most aroma-active compounds contributing to the aroma of clear type pork stock detected by AEDA and subsequent omission and addition experiments.